A switched quasi Z-source three-port (SqZSTP) DC-DC converter for a photovoltaic power generation system. (1st April 2022) - Dhinesh, V; Vijayakumar, G
Abstract: In this paper, a modified wide-input switched quasi Z-source three-port (SqZSTP) DC-DC converter is proposed to interface a photovoltaic inverter with a distributed power generation system. The proposed SqZSTP DC-DC converter constructed with a quasi Z-source impedance network and a three-winding high-frequency transformer offers high voltage gain over a wide input voltage range. In the proposed topology, the input port is divided into two ports, to reduce the power rating and voltage stress across each component. The design and operating principles of the SqZSTP DC-DC converter are presented. The steady state and dynamic performance of the proposed SqZSTP DC-DC converter are compared to other converters that have an impedance network in front. The fuzzy logic controller used in the voltage loop avoids variation in the output voltage when a wide variation in the input voltage happens. In order to test the proposed topology, a scaled-down model with a voltage and power rating of 400 V/1400 W was developed. AT conversion efficiency of 94.5% is achieved.